Delayed mortality among solid organ transplant recipients hospitalized for COVID-19 - VELİOĞLU, ARZU (My University, 2022)
Introduction: Most studies of solid organ transplant (SOT) recipients with COVID-19 focus on outcomes within one month of illness onset. Delayed mortality in SOT recipients hospitalized for COVID-19 has not been fully examined. Methods: We used data from a multicenter registry to calculate mortality by 90 days following initial SARS-CoV-2 detection in SOT recipients hospitalized for COVID-19 and developed multivariable Cox proportional-hazards models to compare risk factors for death by days 28 and 90. Results: Vital status at day 90 was available for 936 of 1117 (84%) SOT recipients hospitalized for COVID-19: 190 of 936 (20%) died by 28 days and an additional 56 of 246 deaths (23%) occurred between days 29 and 90. Factors associated with mortality by day 90 included: age > 65 years [aHR 1.8 (1.3-2.4), p =<0.001], lung transplant (vs. non-lung transplant) [aHR 1.5 (1.0-2.3), p=0.05], heart failure [aHR 1.9 (1.2-2.9), p=0.006], chronic lung disease [aHR 2.3 (1.5-3.6), p<0.001] and body mass index ≥ 30 kg/m2 [aHR 1.5 (1.1-2.0), p=0.02]. These associations were similar for mortality by day 28. Compared to diagnosis during early 2020 (March 1-June 19, 2020), diagnosis during late 2020 (June 20-December 31, 2020) was associated with lower mortality by day 28 [aHR 0.7 (0.5-1.0, p=0.04] but not by day 90 [aHR 0.9 (0.7-1.3), p=0.61]. Conclusions: In SOT recipients hospitalized for COVID-19, >20% of deaths occurred between 28 and 90 days following SARS-CoV-2 diagnosis. Future investigations should consider extending follow-up duration to 90 days for more complete mortality assessment.